2014
DOI: 10.1007/s00438-014-0925-2
|View full text |Cite
|
Sign up to set email alerts
|

Y-SNP L1034: limited genetic link between Mansi and Hungarian-speaking populations

Abstract: Genetic studies noted that the Hungarian Y-chromosomal gene pool significantly differs from other Uralic-speaking populations. Hungarians show very limited or no presence of haplogroup N-Tat, which is frequent among other Uralic-speaking populations. We proposed that some genetic links need to be observed between the linguistically related Hungarian and Mansi populations.This is the first attempt to divide haplogroup N-Tat into subhaplogroups by testing new downstream SNP markers L708 and L1034. Sixty Northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The possible genetic relation of modern Hungarians to Finno-Ugric groups was tested in several studies [ 6 8 ], however all these found Hungarians being genetically unrelated to Uralic people. One of the latest studies [ 9 ] reported that a Y-chromosome haplogroup ( N-L1034 ) is shared between 4% of the Hungarian Seklers (Hungarian-speaking ethnic group living in Transylvania) and 15% of the closest language relatives the Mansis, though the same marker is also present in Central Asian Uzbeks and has been detected just in one Hungarian [ 10 ]. These results indicated that Uralic genetic links hardly exist in modern Hungarians.…”
Section: Introductionmentioning
confidence: 99%
“…The possible genetic relation of modern Hungarians to Finno-Ugric groups was tested in several studies [ 6 8 ], however all these found Hungarians being genetically unrelated to Uralic people. One of the latest studies [ 9 ] reported that a Y-chromosome haplogroup ( N-L1034 ) is shared between 4% of the Hungarian Seklers (Hungarian-speaking ethnic group living in Transylvania) and 15% of the closest language relatives the Mansis, though the same marker is also present in Central Asian Uzbeks and has been detected just in one Hungarian [ 10 ]. These results indicated that Uralic genetic links hardly exist in modern Hungarians.…”
Section: Introductionmentioning
confidence: 99%
“…S12, Supplementary Table S8). Based on MJ of 17 Y-STR loci, certain samples show identical or one-step neighbour profiles to Bashkirs, Khantys 17 , Hungarians 34 , Tatars from Volga-Ural region and a Central Russian sample 17 (Fig. 6).…”
Section: The Possible Maternal Genetic Connection Of South-ural Regiomentioning
confidence: 99%
“…Genetic testing of the modern Hungarian populations' paternal lineage showed either no or very low frequency of the (Zerjal et al 1997;Semino et al 2000;Csányi et al 2008;Fehér et al 2015;Pamjav et al 2017), which is dominant in all the other Finno-Ugric populations (Zerjal et al 1997). On the other hand, it is noteworthy that in one study, the N-Tat (M46) Y-chromosomal marker was found in 50% of the investigated tenth century CE classic Hungarian Conquerors (Csányi et al 2008).…”
Section: Introductionmentioning
confidence: 99%